"A double burden, a double cross" : Andrei Sobol as a Russian-Jewish writer - Khazan, Vladimir (Jews of Russia & Eastern Europe and their legacy., 2017)
A comprehensive and exhaustive account of Andrei Sobol's public, literary, and artistic activities as a purely Russian-Jewish phenomenon. Khazan analyzes his biographical subject within the framework of cultural studies.